Kualitas Hidup ODHA Di Kecamatan Bongas - Carsita, Wenny Nugrahati; Kusmiran, Mirah Asmi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
HIV / AIDS is a chronic disease that can affect all aspects of a person's life. Bongas is a sub-district with the highest number of cases compared to other sub-districts in Indramayu Regency. HIV / AIDS is reported to not only cause symptoms and complications but also has a negative impact on quality of life. Quality of life will affect the health condition of people living with HIV, especially in treatment programs. The aim of this study was to determine the quality of life of PLWHA in Bongas. This study used a quantitative research with descriptive approach. The sample amounted to 165 respondents with taking consecutive sampling technique. The results of the study were 118 (71.5%) respondents had a good quality of life in physical domain, 84 (50.9%) respondents had a good quality of life in psychological domain, 124 (75.2%) respondents had a good quality of life in social domain, 93 (56.4%) had a good quality of life in the independence domain, 86 (52.1%) respondents had a good quality of life in the environmental domain, and 86 (52.1%) respondents had a good quality of life in the spiritual domain. The conclusion of this study is that PLWHA in Bongas have a good quality of life. Keywords: Quality of Life, PLWHA